Exposure-based Interventions for the management of individuals with high levels of needle fear across the lifespan: a clinical practice guideline and call for further research. Issue 3 (3rd May 2016) - McMurtry, C. Meghan; Taddio, Anna; Noel, Melanie; Antony, Martin M.; Chambers, Christine T.; Asmundson, Gordon J. G.; Pillai Riddell, Rebecca; Shah, Vibhuti; MacDonald, Noni E.; Rogers, Jess; Bucci, Lucie M.; Mousmanis, Patricia; et al.
Abstract: Needle fear typically begins in childhood and represents an important health-related issue across the lifespan. Individuals who are highly fearful of needles frequently avoid health care. Although guidance exists for managing needle pain and fear during procedures, the most highly fearful may refuse or abstain from such procedures. The purpose of a clinical practice guideline (CPG) is to provide actionable instruction on the management of a particular health concern; this guidance emerges from a systematic process. Using evidence from a rigorous systematic review interpreted by an expert panel, this CPG provides recommendations on exposure-based interventions for high levels of needle fear in children and adults. The AGREE-II, GRADE, and Cochrane methodologies were used. Exposure-based interventions were included. The included evidence was very low quality on average. Strong recommendations include the following. In vivo (live/in person) exposure-based therapy is recommended (vs. no treatment) for children seven years and older and adults with high levels of needle fear. Non- in vivo (imaginal, computer-based) exposure (vs. no treatment) is recommended for individuals (over seven years of age) who are unwilling to undergo in vivo exposure. Although there were no included trials which examined children < 7 years, exposure-based interventions are discussed as good clinical practice. Implementation considerations are discussed and clinical tools are provided. Utilization of these recommended practices may lead to improved health outcomes due to better health care compliance. Research on the understanding and treatment of high levels of needle fear is urgently needed; specific recommendations are provided.